Pengembangan Media Pembelajaran Power Point Personal Presentation Untuk Mencapai Aktivitas Belajar Siswa - Fadila Nurunnisa; Asep Hidayat; Bella Anantha Sritumini (EDUCARE, 2013)
Learning activities involve asking, listening, commenting, answering, refuting, writing, and activities that can achieve students' interest and motivation in learning, while teaching activities are activities carried out by teachers in providing and delivering learning materials, but those who process and do so. students, teachers only as facilitators and mentors in learning activities so students are able to develop their talents and potential. This study aims to achieve learning activities of class XI students of Bina Warga Bandung Vocational School in learning by using power point personal presentation learning media. This is expected to help teachers so that students do more of the learning activities they should. The results of the study were obtained from (1) Development of power point personal presentation learning media, (2) The use of power point personal presentation learning media, (3) Student learning activities, (4) The results of student learning activities using the power point personal presentation learning media.From these data it can be concluded that the use of learning media power point personal presentation can achieve student learning activities.